Coding for Kids sebagai Proses Pengenalan Pemrograman Komputer bagi Siswa Sekolah Al Masduqi Boarding School (AMBS) - Garut - Nugraha, Agus (LPPM Universitas Koperasi Indonesia, 2024)
The teaching and learning process (PBM) for students at Al Masduqi Boarding School (AMBS) - Garut is held intra-curricular and extra-curricular. One of the extra-curricular activities (ekskul) is Coding for Kids (Ekskul Koding) where this activity is managed by the school involving a team that is competent in the field of computer programming. As a PBM, the implementation of coding extracurricular activities must consider and implement the functions of primary and secondary education. The team plans this by preparing Terms of Reference (ToR) which contain the background, aims and objectives, educational methods and the team and instructors involved and the overall series of activities. In the Odd Semester of the 2023/2024 Academic Year, as many as 8 students took part in this activity which was guided by 1 – 2 instructors with a meeting frequency of once a week for an average of 90 minutes. During activities, students are monitored and evaluated by a team consisting of Deputy Director I for Curriculum, Extra-Curricular Coordinator and Instructor.